Proposta de gerenciamento de efluentes de serviços de saúde, gerados no Hospital Universitário Regional de Maringá (HUM) - Abreu, Elenice Tavares (2008)
Most of the chemicals used in the health establishments are discharged in the sewage collection networks. The identification of the generation points of effluents and their characterization enabled the assessment of the impact that their discharge may cause to the environment and which hospital's sectors should be adjusted, according the management plan of effluents. The objective of this work was to formulate a plan for the management of health service effluents, generated in the Hospital Universitário Regional de Maringá (HUM). The results of the characterization of medicines consumption in the hospital showed that a significant amount of antibiotic was used, presenting itself as the largest quantity of drugs used in HUM. Twenty composed samples of the HUM effluent was collected in 2006 and five samples in 2007. During the collections, pH and temperature were measured. For these samples, bacteriological and physical-chemical analysis, such as pH, turbidity, apparent and real color, total solids, suspended solids, chemical oxygen demand (COD), total nitrogen and total phenols, were accomplished. In the first and in the second phase, 39 and 29 colonies were identified, respectively, in the collected samples of effluents. The analysis of bacterial identification indicated that the Klebsiella pneumoniae was the bacterium species present in higher percentage in the effluent samples collected in HUM. The resistance rate of the bacteria to the antibiotic gentamicin was 28%, in both phases. The bacteria presented greater sensitivity to the antibiotic Meropenem, which performed activities of 97 and 100% on the identified bacteria. The results of the physical-chemical analysis showed that these effluents present average total solids concentration of 888 mg/L, Chemical Oxygen Demand of 974 mg/L O2, Total Nitrogen concentration of 53 mg/L and average concentrations of Total Phenols of 8,8 mg /L. Considering the information on the generated effluents, according to the hospital's activities, and their characterization, the need of implementation of a management plan of the effluents was identified, aiming the minimization and segregation of effluents, making possible their future treatment.